Pengaruh Permainan Al-Asrar Al-Mutasalsilahah terhadap Keterampilan Mendengar Bahasa Arab Siswa - Fahrur Rosikh; Alif Kafa Thoyyibah; Muhimmatus Sholihah (Program Studi Pendidikan Bahasa Arab bekerjasama dengan Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Institut Pesantren Sunan Drajat Lamongan., 2021)
This study aims to determine the effect of the application of the whisper-chain game (al-asrar al-mutassilah) on improving students' listening skills in learning Arabic. In an effort to improve students' skills in learning Arabic, various methods are needed, including the application of active and interactive learning methods and techniques. Nowadays, various methods and techniques in learning that can be applied have emerged, including playing techniques. This study uses an experimental method with the subject of this research being students of class X MA Sabilillah Kebonsari Sukodadi Lamongan. Data were collected using test, documentation, and observation techniques. The results of this study indicate that the whispering game (al-asrar al-mutasalilah) is effective in improving the listening skills of the tenth grade students of MA Sabilillah Kebonsari Sukodadi Lamongan in learning Arabic